IMF-Supported Programs and Income Convergence in Low-Income Countries - Pradhan, Tejesh (IMF Working Papers; Working Paper, 2018)
Continuing the empirical debate on the effects of IMF-supported programs on participating countries' macroeconomic performance, we focus on the issue of whether these programs accelerate conditional AY-convergence among low-income countries (LICs). We use an unbalanced panel dataset for 85 LICs over the period 1986-2015 and employ two different econometric methods to address the selection bias problem. Our empirical results suggest that the rate of conditional income per capita convergence is faster among LICs with extended IMF support than that in countries without support or with intermittent support.